Empowerment of Ratu Kinasih Studio as a Media for Introducing Gulma Penida Dance for Tourists in Lembongan Village Nusa Penida Klungkung - I Gusti Ngurah Sudibya; Ni Made Arshiniwati; Ni Luh Sustiawati (Mudra Jurnal Seni Budaya, 2023)
The empowerment of the Ratu Kinasih studio through the Gulma Penida dance training is expected to be able to enrich the types of dance that previously existed in Nusa Penida and can also be presented as entertainment to tourists visiting Nusa Penida. The benefit of this program is that it can channel creativity; increase knowledge and skills of dance art; promote more interesting traditional dances with meaningful movements from the potential of local wisdom that has never been published; and be an attraction for foreign and local tourists. Empowerment of the Gulma Penida dance was carried out in Lembongan Village, a coastal area with the local wisdom of cultivating seaweed that has been practiced for a long time. Besides that, Nusa Penida is also known for its woven cloth crafts made by residents in Karang Ampel Village. The two potentials in Nusa Penida, namely the potential for seaweed farming and the craft of woven cloth, have been used as a source of ideas in the creation of the Gulma Penida dance. The implementation of this empowerment was carried out from April to August 2022. The empowerment program participants totaled 12 people. From this empowerment program, the result shows that students are skilled at dancing the Gulma Penida dance and can promote the Gulma Penida dance.